Edible bird nest protects the kidney from gentamicin induced acute tubular necrosis - Lim, Christopher Thiam Seong; Mohtarrudin, Norhafizah; Sani, Dahiru; Tan, S. N.; Lim, Chee Woei; Kirby, Brian P.; Ideris, Aini; Stanslas, Johnson (Frontiers Media, 2021)
Every year, there are about 13.3 million cases of acute kidney injury (AKI). Although AKI is a preventable and treatable disease, if left untreated, it has high risk of multiple organ failure and progression to end stage kidney disease. Acute tubular necrosis (ATN) has been recognised as one of the major causes of AKI. Till to date, there is no effective supplement or medication in treating or reversing AKI. Most of the treatment strategies involve preventative measure to minimise the occurrence of AKI or to reverse the cause of AKI. Hence one of the primary area of research interests is to explore the potential treatment for AKI. Edible bird nests (EBN) are edible food produce by the swiftlet’s saliva, which is rich in sialic acids. Sialic acids are monosaccharides that play a vital role in maintaining the integrity and proper function of the human organs, including kidneys. EBN also contains epidermal growth factor, which is widely believed to have rejuvenation and tissue repairing properties. We initiate this study to study the potential reno-protective effect of edible bird’s nests by studying the Wistar rat model of gentamicin-induced AKI. Besides renal profiles, renal histology was also semiquantitatively assessed. In our study, pre-treatment with EBN prevented and ameliorated the gentamicin-induced AKI. To a lesser extent, post-treatment with EBN also protected the kidney from the toxic effect of gentamicin. Our findings are highly indicative that EBN possesses reno-protective properties.